A Group Theory Approach towards Some Rational Difference Equations - Mensah Folly-Gbetoula; Nkosingiphile Mnguni; A. H. Kara (Journal of Mathematics)
A full Lie point symmetry analysis of rational difference equations is performed. Nontrivial symmetries are derived, and exact solutions using these symmetries are obtained.